URGENSI KAJIAN NASIKH DAN MANSUKH DALAM BINGKAI GENERASI KEKINIAN (Upaya Membumikan Teori Klasik Untuk Masa Kini) - Sefri Auliya; Hidayatul Azizah Gazali (Islam Transformatif : Journal of Islamic Studies, 2018)
Ta’arudh (contradiction in understanding) between the ulama in understanding the syara texts' especially in the interpretation of the Koran became one of the principles of the birth of nasikh and mansukh theories. This article contains an analytical descriptive explanation of Nasakh, namely a statement that indicates the existence of an annulment of existing law, then nasikh, namely the argument that comes later that removes and replaces the existing law and mansukh, namely the previous law which has been deleted and replaced by the coming argument after that. Correct knowledge of the text that is nhurical and which can help one in understanding the context of the passage of a text of the Qur'an and can also know which part of the text of the Qur'an comes down first and which comes down later. Besides that, the knowledge of the Nasakh will also strengthen our belief that the source of the Qur'an which is essential is from Allah SWT. He is the one who removes a verse and replaces it with others according to His will. The problem of nasikh and mansukh is not something that stands alone, it is a part that is in the disciplines of interpretation and the science of ushul fiqh. Knowledge of nasikh and mansukh is very useful so that knowledge about the law is not chaotic and blurred. Therefore there are many atsar (sayings of friends) that encourage to know this problem. Especially for the present, knowledge of this theory is needed so as not to carelessly swallow and regurgitate the Qur'anic verses so that it is feared that it can tarnish its sanctity.